2163. Risk Factors for Carbapenem-Resistant Gram-Negative Bloodstream Infections (BSI) in U.S. Hospitals (2010–2015). (26th November 2018) - Cai, Bin; Echols, Roger; Rudin, Deborah; Morgan, Gareth; Nagata, Tsutae
Abstract: Background: Carbapenem-resistant (CR) Gram-negative (GN) infections are associated with higher mortality and extended hospital stays. Time to effective antibiotic treatment is important for patient survival. Classifying the risk factors for CR GN BSI before identification and susceptibility results are known is critical; this study explores the risk factors associated with CR GN BSI in U.S. hospitals. Methods: BSI caused by 11 of the most common GN pathogens were identified from 181 acute care hospitals that contributed microbiology and susceptibility test data to the Premier Healthcare Database 2010–2015. We used univariate analyses to select potential risk factors and a multivariate logistic regression model to predict CR BSI with these risk factors. Results: Among 46, 199 patients with GN BSI, 1, 592 (3.6%) had CR pathogens. From univariate analyses, the significant factors ( P -value <0.05) when comparing CR vs. carbapenem susceptible (CS) infections were age, race, gender, geographic location, admission source, Charlson Comorbidity Index, having BSI while in the ICU or after having stayed in the ICU, and index culture day. Adjusted odds ratios (OR) from multiple logistic regression are shown below. Conclusion: Patients with CR GN BSIs were more likely to be of a younger age group, transferred from a health care facility, stayed in ICU, and had positive BSI culture more than 48 hours after admission. Risk of CR BSI increased for patients with congestive heart failure, peripheral vascular disease, dementia, renal disease, and any malignancy. Disclosures: All authors: No reported disclosures.